Self-imposed contribution in Slovenian and Serbian legislation - Podlipnik, Jernej (Lex localis, 2018)
Sometimes, in order to provide themselves better living conditions, the residents of a certain municipality may be willing to pay an additional fiscal levy besides ordinary taxes. In this paper, the authors deal with a self-imposed contribution as a possible resource of local budgets, comparing the regulation and concept of such a contribution in Slovenia and Serbia. By analysing the characteristics of such a levy in these two former Yugoslav states, the authors based their main hypothesis on proving that self-imposed contribution is, according to its legal nature, also a type of a tax, even if it is introduced under a referendum and the funds are earmarked for specific local purposes.
Keywords: davki; tax; lokali proračuni; Srbija; Serbia; Slovenia; Slovenija; lokalna samouprava; local government